2019
DOI: 10.1111/pcn.12823
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate hypothesis in schizophrenia

Abstract: Schizophrenia is a chronic and severe psychiatric disorder that has profound impact on an individual’s life and on society. Thus, developing more effective therapeutic interventions is essential. Over the past quarter‐century, an abundance of evidence from pharmacologic challenges, post‐mortem studies, brain imaging, and genetic studies supports the role of glutamatergic dysregulation in the pathophysiology of schizophrenia, and the results of recent randomized clinical trials based on this evidence have yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
172
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(204 citation statements)
references
References 191 publications
6
172
0
7
Order By: Relevance
“…Specifically, combined TMS-EEG has permitted the development of novel neuromodulation targeted at non-motor areas, 144 suggesting that it can be used for expansion of the range of stimulation protocols. Further elucidation of the effects of neuromodulation on TEP-related biomarkers could be helpful to the application of TMS-EEG as a useful biometric to assess clinical effectiveness in a wide range of neuropsychiatric disorders, including major depression, bipolar disorder, 145 schizophrenia, 146 addiction, autism spectrum disorders, attention deficit hyperactivity disorder, and mild cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, combined TMS-EEG has permitted the development of novel neuromodulation targeted at non-motor areas, 144 suggesting that it can be used for expansion of the range of stimulation protocols. Further elucidation of the effects of neuromodulation on TEP-related biomarkers could be helpful to the application of TMS-EEG as a useful biometric to assess clinical effectiveness in a wide range of neuropsychiatric disorders, including major depression, bipolar disorder, 145 schizophrenia, 146 addiction, autism spectrum disorders, attention deficit hyperactivity disorder, and mild cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, MMN amplitude reduction has been considered to represent NMDA‐type glutamate receptor (NMDAR) hypofunction . Impaired glutamatergic neurotransmission is thought to be a significant cause of schizophrenia because noncompetitive antagonists of the NMDAR induce schizophrenia‐like symptoms including cognitive impairment .…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, MMN amplitude reduction has been considered to represent NMDA-type glutamate receptor (NMDAR) hypofunction. 29 Impaired glutamatergic neurotransmission is thought to be a significant cause of schizophrenia because noncompetitive antagonists of the NMDAR induce schizophrenia-like symptoms including cognitive impairment. 29 Our findings in nonhuman animals contribute to the establishment of MMN as a translational biomarker that reflects trait and state in psychiatric disorders, leading to the development of new drugs (eg, NMDAR-targeted) and therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Synapse dysfunction, in particular dopaminergic neurotransmission dysregulation (Snyder, ), impairment of glutamatergic neurons (Uno & Coyle, ), and abnormalities of neuronal connectivity involving interneurons in the hippocampus and prefrontal cortex (Mukherjee et al , ) have been suggested to underline the pathophysiology of schizophrenia. As a matter of fact, the first antipsychotic drug, chlorpromazine, was shown to block dopamine receptors (Carlsson, ).…”
Section: Validation Of the Sulfide Stress Hypothesis In Mouse Modelsmentioning
confidence: 99%
“…In spite of current treatment that largely consists in antipsychotic drugs combined with psychological therapies, social support, and rehabilitation, developing more effective therapeutic interventions is an essential issue. EMBO Mol Med (2019) 11: e10983 See also: M Ide et al (December 2019) S ynapse dysfunction, in particular dopaminergic neurotransmission dysregulation (Snyder, 1976), impairment of glutamatergic neurons (Uno & Coyle, 2019), and abnormalities of neuronal connectivity involving interneurons in the hippocampus and prefrontal cortex (Mukherjee et al, 2019) have been suggested to underline the pathophysiology of schizophrenia. As a matter of fact, the first antipsychotic drug, chlorpromazine, was shown to block dopamine receptors (Carlsson, 2001).…”
mentioning
confidence: 99%